In Silico Study of the Interaction Between Human 5-HT2C Receptor and Antidepressant Drug Candidates - Barros, Romulo; Costa, Jhonatan; Pereira, Wildrimak; Mendes, Diego; Cardoso Júnior, Fábio; Ramos, Ricardo (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS); 2019: Anais da VII Escola Regional de Computação Aplicada à Saúde, 2019)
Depression is a major public health concern affecting 300 million people worldwide, according to WHO. The mechanism of depression is presumed to be related to the role of serotonin (5-hydroxytryptamine - 5-HT) and its receptors in the central nervous system. In this work a human 5-HT2C receptor model was created by homology modeling, and molecular docking studies were performed with the ligands fulvic acid, paroxetine, citalopram, and serotonin itself. Fulvic acid had similar affinity parameters to paroxetine and s-citalopram, which are widely used drugs for the treatment of psychiatric disorders such as depression and anxiety.